Correlação entre achados ecocardiográficos de função ventricular esquerda e aptidão aeróbica em indivíduos diabéticos - Petronilho, Ariane (Universidade Federal de São Carlos, 2021)
Background: Type 2 diabetes mellitus is a chronic disease capable of causing micro and macrovascular complications, in addition to abnormalities in cardiac function that directly impact aerobic fitness. Studies show that diabetic individuals have abnormalities in left ventricular diastolic function and myocardial strain that normally precede the appearance of abnormalities in the left ventricular ejection fraction, and that these abnormalities may be related to the lower aerobic fitness presented by diabetic individuals with preserved ejection fraction. Aerobic fitness can be assessed through oxygen consumption kinetics, which shows the speed of adjustment of the cardiovascular, pulmonary, and musculoskeletal systems against a given energy demand, with a faster adjustment speed representing better aerobic fitness. Objective: to correlate aerobic fitness responses with left ventricular function parameters in diabetic individuals. Casuistry and Methods: The studied population consisted of 10 type 2 diabetic individuals and 11 healthy individuals aged between 30 and 65 years old Anamnesis, blood tests, echocardiographic examination, and cardiopulmonary exercise test (CPET) were performed. The CPET protocol consisted of an incremental load phase to determine the maximum oxygen consumption and the gas exchange threshold, and a constant load phase (supramaximum test) to confirm the maximum oxygen consumption reached. Aerobic fitness was assessed by determining the kinetics of oxygen consumption and heart rate using the Mean Normalized Gain (MNG), and calculating the ԏ (tau), during a binary pseudorandom protocol. Data were analyzed using the Mann-Whitney test and Kendal's tau correlation coefficient. Results: We observed that diabetic individuals have lower aerobic fitness (lower MNG values), as well as systolic dysfunction due to abnormalities on global longitudinal strain and incipient signs of left ventricular diastolic dysfunction (lower E wave and E/A ratio values, and higher A wave values). We showed a positive correlation between systolic function (strain) and aerobic fitness (MNG). Conclusions: Normotensive diabetic individuals, with incipient signs of diastolic ventricular dysfunction and with systolic dysfunction, have lower aerobic fitness. Changes in global longitudinal strain were correlated with lower aerobic fitness.
Correlation between echocardiographic findings of left ventricular function and aerobic fitness in diabetic individuals
Keywords: Exercício físico; Diabetes mellitus; Ecodopplercardiograma; Disfunção diastólica; Strain longitudinal global; Cinética do consumo de oxigênio; Physical exercise; Echodopplercardiogram; Diastolic dysfunction; Global longitudinal strain; Oxygen consumption kinetics; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::MEDICINA